2014
DOI: 10.1021/jo4026012
|View full text |Cite
|
Sign up to set email alerts
|

Bidentate Urea Derivatives of p-tert-Butyldihomooxacalix[4]arene: Neutral Receptors for Anion Complexation

Abstract: Three new bidentate ureidodihomooxacalix[4]arene derivatives (phenyl 5a, n-propyl 5b, and tert-butyl 5c) were synthesized in four steps from the parent compound p-tert-butyldihomooxacalix[4]arene and obtained in the cone conformation, as shown by NMR studies. The binding ability of these neutral receptors toward spherical, linear, trigonal planar, and tetrahedrical anions was assessed by (1)H NMR and UV-vis titrations. The structures and complexation energies of some complexes were also studied by DFT methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 36 publications
6
30
0
Order By: Relevance
“…The data (Table ) showed that tert ‐butyl urea 4c , obtained in the partial cone conformation, is a weak receptor displaying very low association constants (log K ass ≤ 1). These results are in line with those obtained with bidentate tert ‐butyl ureido‐dihomooxa receptors,, also having only two urea moieties. The type of substituent (aryl/alkyl) at the urea unit strongly affects the association constants.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The data (Table ) showed that tert ‐butyl urea 4c , obtained in the partial cone conformation, is a weak receptor displaying very low association constants (log K ass ≤ 1). These results are in line with those obtained with bidentate tert ‐butyl ureido‐dihomooxa receptors,, also having only two urea moieties. The type of substituent (aryl/alkyl) at the urea unit strongly affects the association constants.…”
Section: Resultssupporting
confidence: 90%
“…As part of our interest in the study of homooxacalixarenes (calixarene analogues in which the CH 2 bridges are partly or completely replaced by CH 2 OCH 2 groups) we have reported the anion binding affinity of several di‐, and tetra‐substituted (thio)ureido‐dihomooxacalix[4]arenes, in the cone conformation incorporating a four carbon atom spacer. Tetra‐substituted dihomooxa receptors in a partial cone conformation and bearing a propyl spacer were also studied .…”
Section: Introductionmentioning
confidence: 99%
“…These macrocycles possess an intermediate size between those of calix [4]-and - [5]arenes. In recent work, 15,16 the binding abilities of dihomooxacalix [4]arene bidentate urea derivatives showed a dependence on both basicity and geometrical features of anions. Also, as expected due to the higher acidity of their NH groups, arylureas showed higher K b values compared with alkylureas.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is noteworthy that in the case of compounds 9 and 10, only urea-containing residues were considered (Scheme 3), as they provide the specific anionbinding site of the dihomooxacalix [4]arene compounds under study as has been referred in previous work. 15 Theoretical estimates are presented in Tables 2 and 3. (Table 1); this tendency was expected, and it is exemplified using experimental data for the binding with urea compounds 9…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] One should note also heteracalixarenes, i.e. thia-, aza-and homooxa-calixarenes containing S, N and O heteroatoms in their structures, [26][27][28] . They have recently attracted considerable attention due to their easy accessibility and versatile receptor properties.…”
Section: Introductionmentioning
confidence: 99%